Purified Neurons can Survive on Peptide‐Free Graphene Layers. Issue 7 (8th January 2013) - Bendali, Amel; Hess, Lucas H.; Seifert, Max; Forster, Valerie; Stephan, Anne‐Fleur; Garrido, Jose A.; Picaud, Serge
<x xml:space="preserve">Abstract</x> The excellent cytocompatibility of single‐layer CVD graphene is demonstrated by showing that primary adult retinal ganglion cells can directly survive on its surface without any supporting glial layer or protein coating. These results confirm the great potential of graphene as a biocompatible material for interfacing neurons, opening a new route for the development of a novel generation of flexible and high‐sensitive neural prostheses. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>